Theorie and Applications of Formal Argumentation First International Workshop, TAFA 2011. Barcelona, Spain, July 16-17, 2011, Revised Selected Papers - Modgil, Sanjay; Oren, Nir.; Toni, Francesca; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the thoroughly refereed proceedings of the First International Workshop on the Theory and Applications of Formal Argumentation, TAFA 2011, held in Barcelona, Spain, in Juli 2011, as a workshop at IJCAI 2011, the 22nd International Joint Conference on Artificial Intelligence. The 9 revised full papers presented together with 8 revised poster papers were carefully selected during two rounds of reviewing and improvement from 32 initial submissions. The workshop promotes and fosters uptake of argumentation as a viable AI paradigm with wide ranging application, and provides a forum for further development of ideas and the initiation of new and innovative collaborations. The papers cover the following topics: properties of formal models of argumentation; instantiations of abstract argumentation frameworks; relationships among different argumentation frameworks; practical applications of formal models of argumentation; argumentation and other artificial intelligence techniques; evaluation of formal models of argumentation; validation and evaluation of applications of argumentation.
Keywords: Computer science; Computer Communication Networks; Data mining; Artificial intelligence; Law; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery; Computer Communication Networks; Computers and Society; Law, general